2022
DOI: 10.1136/bjo-2022-321415
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of the fluocinolone acetonide intravitreal implant (ILUVIEN): 3-year results from the European IRISS registry study

Abstract: BackgroundThe ILUVIEN Registry Safety Study was a multicentre, open-label, non-randomised, observational, phase 4 study designed to assess the safety and effectiveness of the fluocinolone acetonide (FAc) implant in all indications in real-world practices in Europe.MethodsThe study included data collected prospectively and retrospectively. Patients receiving FAc implants between 2013 and 2017 were included and monitored until the last patient reached ≥3 years of follow-up. Mean intraocular pressure (IOP) data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The clinical efficacy of the Iluvien intravitreal insert has been demonstrated by other RCTs and several real-life observational studies [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ] and confirmed by systematic reviews, meta-analyses, and expert panels [ 142 , 143 , 144 ].…”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 77%
See 4 more Smart Citations
“…The clinical efficacy of the Iluvien intravitreal insert has been demonstrated by other RCTs and several real-life observational studies [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ] and confirmed by systematic reviews, meta-analyses, and expert panels [ 142 , 143 , 144 ].…”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 77%
“…Iluvien has shown higher effectiveness in chronic (>3 years duration) DME eyes [ 40 ] and has provided both functional and anatomic improvements in DME eyes with persistent DME and refractory to previous therapies with laser, anti-VEGF, or other intravitreal steroids (TA or DEX) [ 133 , 135 , 137 , 138 , 140 , 144 , 145 , 146 ].…”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 99%
See 3 more Smart Citations